Risiko Perbankan, Working Capital Turn Over, dan Profitabilitas - Cahyani, Ni Made Bunga Ayu; Sujana, I Ketut (E-Jurnal Akuntansi, 2021)
This study aims to obtain empirical evidence of the effect of credit risk, liquidity risk, operational risk, and working capital turnover on the profitability of banking companies. The study population was 45 banking companies listed on the Indonesia Stock Exchange (BEI) for the 2015-2019 period. With a purposive sampling technique, this study used 17 samples of companies. Through multiple linear regression analysis techniques, the results show credit risk and operational risk partially have a negative and significant effect on the profitability of banking companies. It means the lower the credit risk and operational risk faced, the greater the profitability can be generated. This study also shows liquidity risk and working capital turnover partially have a positive and insignificant effect on the profitability of banking companies.   This means that the higher the risk of liquidity and working capital turnover faced, will not be able to increase the profitability of banking companies . Keywords: Credit Risk; Liquidity Risk; Operational Risk; Working Capital Turn Over.